Search for the decay B 0 s → η ′ K 0 S - Bhardwaj, Vishal; Patra, Sourav (American Physical Society, 2022)
We report the results of the first search for the decay B 0 s → η ′ K 0 S using 121.4     fb − 1 of data collected at the Υ ( 5 S ) resonance with the Belle detector at the KEKB asymmetric-energy e + e − collider. We observe no signal and set a 90% confidence-level upper limit of 8.16 × 10 − 6 on the B 0 s → η ′ K 0 S branching fraction.
Only IISER Mohali authors are available in the record.
Keywords: B 0 s → η ′ K 0 S; resonance